Does industrialization promote the emission mitigation agenda of East Africa? a pathway toward environmental sustainability - Yu, Yan; Zhao, Jingyi; Musah, Mohammed; Owusu-Akomeah, Michael; Nkyi, Joseph Akwasi; Li, Jing; Appiagyei Ampong, George Oppong; Kumah, Emmanuel Attah; Cao, Siqi; Xu, Yuxiang; Shi, Yingfang; Wang, Liqi; et al. (Frontiers in Environmental Science, 2024)
One macroeconomic variable that has been proven to be a major driver of environmental quality in the world is industrialization. However, despite the numerous explorations on the connection between industrialization and ecological quality, limited studies have examined the linkage amidst the series in East Africa. This study was therefore conducted to help fill that gap. In accomplishing this goal, econometric techniques that control for cross-sectional correlations, heterogeneity and endogeneity among others, were engaged for the analysis. From the results, the panel under consideration was heterogeneous and cross-sectionally correlated. Also, the studied series were first differenced stationary and cointegrated in the long-run. The elasticities of the regressors were explored via the cross-sectionally augmented autoregressive distributed lag (CS-ARDL) estimator, cross-sectionally augmented distributed lag (CS-DL) estimator and the augmented mean group (AMG) estimator. From the results, industrialization reduced environmental quality in the region via high CO2 emissions. Also, financial development, foreign direct investments, urbanization and energy consumption were not environmentally friendly in the bloc. On the causal linkages amid the series, bidirectional causalities between industrialization and CO2 emissions; between energy consumption and CO2 secretions; and between foreign direct investments and CO2 exudates were detected. Finally, one-way causal movements from financial development and urbanization to the effluents of CO2 were unraveled. Based on the findings the study recommended among others that, national policies that can promote energy conservation at the industrial level, and can convert the industrial structure of the region to a low carbon-intensive one should be formulated.